(3OaY Gdede Yf bQGA GdJSgjd HLdH Gdege eeG jbY Hg GdJMUjds - (3CHhGdMSf Ydj Hf eMeO Hf Ydj JQcj, HGj JhfSs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3hHYO, ajbhd Ydj HGTG Hf eMeO Hf Ydj hbO cfJ bjOJ eG JOYh GdMGLI Edjg Ydi ghGeT fSNI dj eYJeOI ef eJf GdJSgjd s
(3BNQgG (B:s
(3hef PG GdPj JQVi SLGjGg cdgG cai GdeQA fHdkG Cf JYO eYGjHg GfJgi GdTQM GdeHGQc s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3Ke JbQjXGJ ddcJGH ef YdeGA eYGUQjf ddTGQMs
(3cdgG HebOGQ (B13 (3hQbIs
(3hHgG fXGe GdJYbjHI s
(3HChdgG agQS ddaUhds
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs